(untitled) (Biological Sciences - PJSIR, 2022)
Date bar is an energy-dense snack food with a high content of carbohydrates and bioactive compounds and deficits protein. The date bar can be fortified with different protein sources and may be used as a functional food product to overcome protein related malnutrition. The present study was conducted to develop protein fortified date bars using skim milk, soybean and almond powders as protein sources and to examine their physico-chemical and sensory characteristics. Four different treatments for protein fortified date bar samples were prepared with different formulations and coded as A (control, 100% date fruit), B (80% date fruit + 20% skim milk powder), C (80% date fruit + 20% soybean powder) and D (80% date fruit + 20% almond powder). Among the treatments, D and C were found to have significantly higher (P<0.05) mean values for most of the physico-chemical properties in comparison to A and B. The average moisture content (18.50%) and carbohydrates (74.02%) remained significantly higher (P<0.05) in A, pH value (6.63) and TSS (28.26 °Brix) in B, ash (2.81%), protein content (12.52%) and vitamin C (11.54 mg/100g) in C and titratable acidity (0.33%), fat content (4.16%) and fibre content (5.15%) in D. The average score for sensory attributes i.e. colour, flavour, texture, aroma and overall acceptability remained significantly higher (P<0.05) in B, while significantly higher (P<0.05) score for taste was recorded in D. It was concluded from the present study that fortification of date bars with different protein sources improved the physico-chemical properties, sensorial attributes particularly protein content of the date bars in comparison to A (control), thus protein-fortified date bars are ideal for human nutrition.